The Application of Guided Inquiry using LKPD on Animal Tissue Topic and its Impact to Science Process Skills and Students' Outcome Learning - Putri, Amalia Nurina; Susanti, R. (Journal of Biology Education, 2020)
According to interview with biology teacher of 11th grade of SMA Negeri 9 Semarang, known that teaching-learning process on animal tissue topic implemented teacher-centered learning, so that low students’ participation in the classroom happened and also there is no laboratory activity which resulted in the low ability of science process. One way to solve that problem is to implement learning model that carry out scientific methods and student-centered learning called guided inquiry. This study aims to analyze the effectiveness of implementation of guided inquiry model using LKPD on students’ science process skills as well as the learning outcomes. The participants are 72 students of 11th grade in science class 5 and 6 of SMA Negeri 9 Semarang in the first semester 2019/2020 academic year. This study used pre-experimental design with One Shoot Case design. Implementation of guided inquiry model using LKPD is effective if ≥ 90% score of science process skills reach a minimum of good criteria and excellent, ≥ 75% of students are able to reach the minimum criteria for completeness of studying (KKM ≥ 70) and enhancement pretest-posttest (N-gain) score are in the medium-high category of ≥ 90% students. The results show science process skills in 97,15% of students reach good and excellent criteria, completeness of studying score in 93,06% of students reach the minimum criteria for completeness of studying (KKM ≥ 70) as well as the enhancement pretest-posttest (N-gain) score in 100% of students are in the middle to high category. This study has identified guided inquiry model using LKPD of animal tissue topic as effective implementation strategy for developing science process skills of students as well as boosting the learning outcomes of students in SMA Negeri 9 Semarang.